19 Pharmaceutical industry payments to thought leaders in cardiovascular disease and diabetes. (4th December 2019) - Karanges, Emily; Ting, Natasha; Parker, Lisa; Fabbri, Alice; Bero, Lisa
Abstract : Objectives: Pharmaceutical industry sponsorship of professional medical associations is prevalent and its impact on medical education and practice has generated widespread concern. Less is known about industry payments to medical practitioners in leadership positions within these organisations, despite their roles as respected thought leaders with influence over clinical norms. Diabetes and cardiovascular disease represent highly profitable markets for industry, with newly-available medicines, large and increasing patient populations, chronic treatment regimens and expanding diagnostic categories. We investigated the extent of pharmaceutical industry payments to leaders of professional medical associations associated with cardiovascular disease and diabetes in Australia. Method: We searched for non-surgical medical associations focused on diabetes or cardiovascular disease, and general professional associations for doctors who routinely manage these conditions, and identified medical practitioners in leadership positions (2016 – 2018) from the associations' websites. Payment details were obtained from publicly-available reports of pharmaceutical industry payments to healthcare professionals (October 2015 – April 2018) downloaded from Medicines Australia, the pharmaceutical trade organisation, and compared against payment disclosures on the associations' websites. Results: We identified 197 leaders from 10 associations; 48 leaders (24.4%) received 467 industry payments, totalling $932, 270. Payments were primarily for chairing/speaking at meetings (240/467 payments; 51.4%) and advisory board participation (118/467; 25.3%). The number and proportion of payment recipients was higher within diabetes associations (24/33; 72.7%) and cardiovascular associations (14/34; 41.2%) in for general associations (7.6%; 10/132). The highest paid association was diabetes-focused and its leaders received a total of $239, 617. The median payment for endocrinologists ($7, 493, IQR: 2, 572 – 20, 534) was approximately half that of cardiologists and GPs. GPs from diabetes societies received a higher median payment ($19, 189, IQR: $11, 341 – $28, 547) than GPs in general associations ($7, 401, IQR: $2, 231 – $32, 484). Only one association disclosed industry funding to leaders on its website, but disclosures were incomplete. Conclusions: A substantial proportion of leaders of cardiovascular- and diabetes-specific societies received pharmaceutical industry payments, raising concerns about industry influence on diagnostic and treatment guidelines, medical education, professional policy and advocacy, and clinical norms. In the context of such far-reaching influence, medical organisations and their leadership have a responsibility to ensure conflicts of interest are disclosed, minimised and managed responsibly.